Kajian Literatur : Efektivitas Cerpen dalam Menumbuhkan Kreativitas Menulis Siswa Kelas IV SD - Salsabilla Cahaya Putri; Nengsi Amelia Nainggolan; Syahroini Syahroini; Syahrial Syahrial (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to examine the effectiveness of using short stories to enhance the writing creativity of fourth-grade elementary students through a literature review approach. It employs a qualitative descriptive method with a non-experimental design. Data were gathered from various written sources such as scientific journals, books, and relevant proceedings, focusing on the role of short stories as a medium for writing instruction. The findings indicate that short stories can stimulate students' imagination, expressive abilities, and narrative understanding through structured plots rich in emotional meaning. Short stories also support students in composing more organized, creative, and expressive narrative texts, in line with the concrete thinking stage of Piaget’s theory. This approach aligns with constructivist principles, as it encourages students to connect personal experiences with story content. In the learning process, short stories are considered more engaging than traditional methods because they create a more interactive and meaningful learning environment. Therefore, the use of short stories has the potential to be an effective instructional strategy in fostering writing creativity and building a strong foundation in literacy from an early age.